THE MODEL OF PERFORMANCE BASED EVALUATION OF CIVIL SERVANTS IN VIETNAM - Dao, Thuy Thi Thanh (Archives of Business Research, 2018)
The performance-based evaluation and payroll systems for government employees formed in the late 1980s in many developed countries. Survey results on strategic human resource management in the 29 OECD countries show that these systems are applied based on individual performance evaluation and one third of OECD countries have developed a performance management system for senior civil servants. This article introduces legal regulations and the application of the performance-based evaluation model for civil servants in Vietnam. The author uses analytical method to justify the significant implications that the research poses in the improvement of the civil servant management regime in Vietnam. The author focuses on researching and clarifying status of the evaluation work after the Law on Cadres and Civil Servants came into force in 2010, points out the shortcomings and causes to formulate renovation and improvement proposals. At the same time, expert method is used by the author to seek advice from managers and experts on human resources management and related issues, identifying the prerequisites for applying the performance-based evaluation system in Vietnam. The author also uses sociological survey method, questionnaire form for civil servants working in four-level authorities. At central level, there are Ministries, including the Ministry of Home Affairs, the Ministry of Health, the Ministry of Labor, Invalids and Social Affairs, the Ministry of Finance, the Ministry of Justice, the Ministry of Agriculture and Rural Development, Ministry of Natural Resources and Environment, the Office of the Government, the State Bank, the State Audit; Localities include provinces: Hai Duong, Ninh Binh, Bac Giang, Hung Yen, Cao Bang, Quang Ninh, Quang Nam, Hue, Daklak, Daknong, and cities under central control: Ha Noi, Hai Phong. The surveyed localities are selected on the basis of ensuring representative for localities with urban and rural characteristics; delta and mountainous areas. Results of this survey support the analysis and evaluation of the situation part.